Impact of integrated nutrient management on growth and flowering of gladiolus (Gladiolus hybrida) cv Novalux - BASOLI, MEENAKSHI; KUMAR, PRABHAT; KUMAR, SANTOSH (The Indian Journal of Agricultural Sciences, 2015)
The present investigation was carried out at Model Floriculture Centre, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, during 2010-11 and 2011-12. The experiment was conducted in simple Randomized Block Design (RBD) with three replications and twenty five treatments consisting of biofertilizers (Azotobacter, PSB and KSB), different levels of inorganic fertilizers, and their combinations. Application of 3/4th N, P and K+ Azotobacter +PSB + KSB (T24) was found most effective in enhancing plant height (112.84 cm), bud emergence (7.31 days), days taken to spike emergence (87.28 days), size of florets (10.22 cm), length of spikes (109.27 cm), rachis length (52.6 cm), chlorophyll content (70.98 SPAD), photosynthetic rate (17.73 Î¼mol/m225). However, maximum number of leaves and days taken for opening of first floret were obtained when plants were fertilized with 3/4thN, P and K+ Azotobacter + PSB (T15). Maximum duration of flowering was obtained with application of 3/4th N, P and K+ Azotobacter + KSB (T18). Treatment 3/4th N, P and K+ PSB + KSB (T21) resulted in maximum stomatal conductance of spikes.